Indication of current-injection lasing from an organic semiconductor - Sandanayaka, Atula S. D.; Matsushima, Toshinori; Bencheikh, Fatima; Terakawa, Shinobu; Potscavage, William J.; Qin, Chuanjiang; Fujihara, Takashi; Goushi, Kenichi; Ribierre, Jean-Charles; Adachi, Chihaya (Applied physics express, 2019)
In this study, we investigate the lasing properties of 4,4′-bis[(N-carbazole)styryl]biphenyl thin films under electrical pumping. The electroluminescent devices incorporate a mixed-order distributed feedback SiO2 grating into an organic light-emitting diode structure and emit blue lasing. The results provide an indication of lasing by direct injection of current into an organic thin film through selection of a high-gain organic semiconductor showing clear separation of the lasing wavelength from significant triplet and polaron absorption and design of a proper feedback structure with low losses at high current densities. This study represents an important advance toward a future organic laser diode technology.